1997
DOI: 10.1021/jf960488g
|View full text |Cite
|
Sign up to set email alerts
|

Content and Composition of Free Sterols and Free Fatty Alcohols in Jojoba Oil

Abstract: A method was developed for the isolation and identification of phytosterols and fatty alcohols in jojoba oil. The method consists in the separation of these compounds from wax esters in the oil by means of an aluminum oxide column followed by further fractionation of the minor components by column chromatography on silica gel. The 4-demethylsterols, 4-methylsterols, triterpene alcohols (4,4-dimethylsterols), and fatty alcohols are identified by means of their gas chromatographic and mass spectrometric data. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The primary phytosterol detected in JO was sitosterol (2.62 mg/g), which comprised 71% of the total phytosterol content. The phytosterol content of JO was in agreement with values reported by Van Boven et al [30]; and the phytosterol content of JO is within the range of most vegetable oils. The principle phytosterol found in SO was also sitosterol (2.09 mg/g), which represents 49% of the total content of phytosterol [31].…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
“…The primary phytosterol detected in JO was sitosterol (2.62 mg/g), which comprised 71% of the total phytosterol content. The phytosterol content of JO was in agreement with values reported by Van Boven et al [30]; and the phytosterol content of JO is within the range of most vegetable oils. The principle phytosterol found in SO was also sitosterol (2.09 mg/g), which represents 49% of the total content of phytosterol [31].…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
“…Based on the retention times and mass spectra of authentic TMS alcohol samples, the peaks at 11.3 min and 14.2 min were identified as being due to trimethylsilylated eicosenol (C20 : 1) and docosenol (C22 : 1), respectively. Peaks at 8.5 min and 17.2 min were considerd to be due to trimethylsilylated octadecenol (C18 : 1) and tetracosenol (C24 : 1), respectively, from comparison of the mass spectra with the NIST 147 database and from the percentage abundance of fragment ions of octadecenol and tetracosenol determined in a previous report 5) , in which the existence of w9 unsaturated fatty alcohols in the jojoba wax esters was proved. The main trimethylsilylated alcohols in the isolated peak fractions corresponded to eicosenol (C20 : 1) in peaks 2 and 3 (Figs.…”
Section: Identification Of the Wax Estersmentioning
confidence: 94%
“…Since it has been reported that the main components of jojoba oil are wax esters 2)῍4) and phytosterols are minor constituents 5) , we used as standard materials synthesized eicosenyl eicosenoate (a wax ester) and a vegetable sterol that is used as a food additive (phytosterols mixture). These standards were both dissolved in hexane at 1 mg/mL.…”
Section: Tlc Analysis Of Jojoba Waxmentioning
confidence: 99%
“…The identification of the various compounds in the different unsaponifiable samples was achieved by comparison of their R f values with reference standards as described by Paganuzzi and Leoni (1979). Sterol fraction was silylilated according to Boven et al (1997). Bis, trimethylsilyl-trifluoroacetamide (BSTFA) and trimethyl-chloro-silan were used for the sylilation procedure.…”
Section: Analytical Determinationsmentioning
confidence: 99%